An observational study on survival rates of patients with out-of-hospital cardiac arrest in the Netherlands after improving the 'chain of survival'. Issue 7 (1st July 2019) - de Visser, Matthijs; Bosch, Jan; Bootsma, Marianne; Cannegieter, Suzanne; van Dijk, Annemarie; Heringhaus, Christian; de Nooij, Jan; Terpstra, Nienke; Peschanski, Nicolas; Burggraaf, Koos
Abstract : Objectives: To evaluate the impact of implemented procedures for out-of-hospital cardiac arrests (OHCAs) by determining patient outcome defined as the percentage return of spontaneous circulation at arrival at the emergency department, and 3-month and 1-year-survival rates. Design: Observational study. Setting: Primary emergency medical care consisting of Advanced Life Support is given by ambulance nurses and secondary care by hospitals within the mid-western part of the Netherlands covering 750 000 inhabitants. Participants: 433 of 500 consecutive patients with OHCA were included in the study over a 1.5 -year period. Outcome measures: Analysis included number of patients with return of spontaneous circulation (ROSC) when handed over to the emergency department, survival at 3 months and 1 year including a comparison with global outcome rates. We further considered the influence of gender, delays, bystander Basic Life Support, use of an automated external defibrillator, initial rhythm and mechanical thorax compression in combination with Boussignac tube ventilation. Results: 13% (67/500) of the initial patient population was excluded from the analysis as reanimation in these patients was aborted due to expressed wish not to be resuscitated. Resuscitation was started by bystanders, police and/or first responders in 312/433 (72%) cases. An automated external defibrillator was used in 198 of these 312 cases (63%) of which it defibrillated 108 times. Mechanical thorax compression in combination with Boussignac tube ventilation was necessary in 277/433 patients (64%). Spontaneous circulation returned in 96/277 (35%) patients of this group. In the overall studied population, ROSC percentage at arrival at the hospital was 214/433 (49%). The 3-month and 12-month-survival rates were 123/433 (28%) and 119/433 (27%), respectively. Conclusions: Optimised 'chain of survival' for patients with OHCA resulted in ROSC in 49% of the cases and a 1-year-survival rate of 27% in the studied population.